Cachexia and Sarcopenia in Companion Animals: An Under‐Utilized Natural Animal Model of Human Disease. Issue 2 (28th November 2018) - Freeman, Lisa M.
Abstract: While laboratory small animal models of cachexia and sarcopenia are well‐suited and critical for studying mechanisms and early pre‐clinical phases for potential treatments, they are not similar enough to the human conditions to always be good predictors for results in human clinical trials. As a result, translational failures can occur when large‐scale human clinical trials are conducted on drugs, even when they appear promising in pre‐clinical studies in rodent models. What is needed is a way to more efficiently and successfully translate information gained from basic science and rodent research into human clinical trials that produce effective approved drugs. Naturally‐occurring cachexia and sarcopenia in companion animals is a more representative model of human disease that can serve as a stepping stone between basic science and human clinical trials. Many of the common diseases of humans also affect companion animals, particularly pet dogs and cats. Pet dogs and cats commonly develop heart failure, cancer, and kidney disease, as well as acute trauma or illness. The population of elderly companion animals also is increasing as pets' lifespans have become longer. As a result, both cachexia and sarcopenia are very common in companion animals. Studying these conditions in dogs and cats – either in colonies or in animal clinical trials ‐ can help to identify successful treatments that can benefit both humans and companion animals.